Pembelajaran Pengetahuan Kreatif M elalui As et Strategis Dalam Menin gkatkan Keunggulan Kompetitif - Mubarok, Muhammad Husni (Universitas Islam Negeri Sunan Kudus, 2017)
This paper develops a creativity-based framework of entrepreneurial learning and knowledge management through strategic asset towards competitive advantage. Entrepreneurial learning, knowledge management and creativity are interdependent. The strength of a firm’s strategic asset help shapes its proficiency to develop creative capabilities of turbulent environments through entrepreneurial learning. Enterprises with strong creative capabilities are intensely entrepreneurial, but instead depend on how firms’ capabilities synergistically combine and transform knowledge resources. Furthermore, this paper aims to integrated the concept of strategic asset, entrepreneurial learning, knowledge management and creative thinking and places bounds on feasibility of particular strategies to sustain superior enterprises competitive advantage in complex and volatile external environments.